ANALISIS PEMANFAATAN MEDIA PEMBELAJARAN DARING BERBASIS GOOGLE CLASSROOM OLEH GURU PADA PEMBELAJARAN SEJARAH DIKELAS XI IPS SMAN 7 PONTIANAK - Puji Lestari Setyaningsih; Nuraini Asriati; Andang Firmansyah (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2022)
AbstractThis study was conducted using descriptive qualitative research methods researchtype, to know the teacher’s perparation bold learning media in history learning, theprocess of implementing teachers in using bold learn the media in the history oflearning, and the obstacles that teachers feel in learning to use learning media thatare bold in history. This search location is in SMAN 7 Pontianak which is locatedon road Sulawesi Dalam No. 10. Data collection techniques used are observation,interviews tools are observation guidelines, interviewguidelines, and studydocuments. The researcher’s data analysis technique used data reduction, datadisplay, and levers. Researchers test the validity of the data using triangulation.From the results of the data, the researcgers know that: (1) To prepare the media asa bold lesson in history learning, the teacher must also prepare the steps forpreparing the implementation of learning (RPP) to adjust to the learning materialthat will later be delivered to raised. (2) Implementation of learning utilizinglearning media does not know all students do understand the material that theteaching conveys because the delivery of the material is too simple and there is nomore in-depth explanation. (3) The use of learning media that has been conveyed bythe teacher is almost the same as what the participants said, use of your learningsupporthistory learning is less effective. (4) In the use of learning means, we oftenfind several sbstacles that become a problem in a learning process, both teahnicallyand non-technically. The usage of google class media under learning is taking intoaccount quite effective, although it has several obstacles. However, this media canhelp teachers stay connected with students and they get lessons that they can learnon their own anywhere and anytime.Keywords: Google Class, Learning History, Media Learning